2020
DOI: 10.1038/s41598-020-69159-9
|View full text |Cite
|
Sign up to set email alerts
|

Transport pathways across the West African Monsoon as revealed by Lagrangian Coherent Structures

Abstract: The West African Monsoon (WAM) system is the main source of rainfall in the agriculturally based region of the Sahel. Understanding transport across the WAM is of crucial importance due to the strong impact of humidity and dust pathways on local cloud formation. However, the description of this transport is challenging due to its 3D complex nature. Lagrangian Coherent Structures (LCS) simplify transport description across the WAM by providing a geometrical partition of the troposphere into domains. Air parcels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…By contrast, the northwesterly subtropical clusters R3 (Harmattan) and S2 (extratropical mid-level dry intrusions) remain around the mixing curves with only slight tendencies towards the Rayleigh curve. This emphasizes the existence of a subtropical mixing barrier that hinders the isotopic exchange between subtropical and tropical transport clusters as discussed in Yang and Pierrehumbert (1994) and Niang et al (2020). The resulting contrast between the e ects of mixing and microphysical processes are well represented in the contours of the full ensemble.…”
Section: Understanding {H 2 O D} Pairs Over the Sahelmentioning
confidence: 69%
See 4 more Smart Citations
“…By contrast, the northwesterly subtropical clusters R3 (Harmattan) and S2 (extratropical mid-level dry intrusions) remain around the mixing curves with only slight tendencies towards the Rayleigh curve. This emphasizes the existence of a subtropical mixing barrier that hinders the isotopic exchange between subtropical and tropical transport clusters as discussed in Yang and Pierrehumbert (1994) and Niang et al (2020). The resulting contrast between the e ects of mixing and microphysical processes are well represented in the contours of the full ensemble.…”
Section: Understanding {H 2 O D} Pairs Over the Sahelmentioning
confidence: 69%
“…The discussion of Fig. 5.1 already showed that COSMO iso simulates markedly di erent isotopic distributions in the Sahelian free troposphere during the three monsoon phases documented in (Sy et al, 2018, Niang et al, 2020, the isotopic composition of cluster S1 merges with the signals of R1. By contrast, the northwesterly subtropical clusters R3 (Harmattan) and S2 (extratropical mid-level dry intrusions) remain around the mixing curves with only slight tendencies towards the Rayleigh curve.…”
Section: Understanding {H 2 O D} Pairs Over the Sahelmentioning
confidence: 81%
See 3 more Smart Citations